SISTEM ORDER DAN PERHITUNGAN JASA SIARAN DAN NON SIARAN BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER 3.1.7 PADA KANTOR LPP RRI MANOKWARI - Marlinda Sanglise (Jurnal Informatika, 2021)
The goal of this study is to find out more about facilitate calculations and orders at the Manokwari LPPRI office by using the Order System and Calculation of Web-Based Broadcast and Non-Broadcast Services Using the CodeIgniter 3.1.7 Framework at the LPP RRI Manokwari Office. The method that was employed in collecting data There is a literature review in this study and interviews. And using the waterfall method as a model development and with mysql as a database. According to the findings It was the case obtained, the results are that It is envisaged that this application would make it easier for users to place orders for broadcast and non-broadcast services.Keywords—system, web, codeigniter, broadcast service